Assessment of Cases Aggrieved with Sexual Crime in Diyarbakır - Yılmaz, Eyyüp; Çelikel, Adnan; Değirmenci, Bülent; Zeren, Cem; Gören, Süleyman (The Bulletin of Legal Medicine, 2011)
The concept of sexual crime emerged through based on sexual abuse or sexual assault is acknowledged as one of the most serious sexual crimes faced by the human being. This study aims to determine socio-demographic allocation characteristics of the cases as victims of sexual crimes with a legal dimension sent from neighbor cities and districts to our local and as well as to exhibit the problems experienced during the process of genital examination and legal psychiatric evaluation. For this purpose, a number ( 16953 ) of forensic cases’ reports assessed which was held in Diyarbakir Division of The Council of Forensic Medicine and inquiry documents (restricted with the cases contacted) as annexes of them were analyzed retrospectively, between January 2010 and December 2011. The cases were classified as childhood age and adult age groups. Results: One-hundred and sixty five (0.97%) of cases belong to judicial cases who were the victim of a sexual crime and included in this study. 73.3% of the cases (n: 121) were female and 26.7% (n:44) were male, while it was determined that the youngest was 3, the oldest was 57 years old. The average age was found as 14.98±7.22 years. The average age of male (12.95± 8.36) cases was lower compared to female (15.72± 6.65) cases (p=0.029). Of the cases 70.3% (n:116) were sent to the judicial examination after 72 hours from the incident and 29.7% (n:49) were sent in a time period before 72 hours. Acute genital evidence was determined in just 9.2% (n:13) of the cases while chronic genital evidence was determined in 20.6% (n:29) of the cases who were applied a genital examination by naked eye. Out of those examined in judicial psychiatric sense 82.8% (n:77) cases were above 18 years old, while it was determined that 17.2% (n: 16) included the cases who were equal or above 19 years old. It was found that 46% (n:76) of individuals who were in a suspected position were familiar people, 18.8% (n:31) was a family member or a close relative. We consider that both genital and psychiatric judicial medical evaluation process of the cases who are sex crime victims requires a more dynamic, sufficiently detail and disciplinary approach. We believe that our current problems related with the process may be diminished by improving and deepening the existing awareness in field of clinical forensic medicine in our country. Key words: Sexual crime, sexual assault, sexual abuse, genital examination, clinical forensic medicine